Repositioning the Tax Court Within Indonesia’s Constitutional Framework: Judicial Independence and Institutional Reform - Gunawan Setiyaji; Ali Abdillah (Lex Publica, 2024)
The 1945 Constitution of the Republic of Indonesia serves as the highest legal foundation, outlining state objectives and the role of judicial institutions. However, the Tax Court, established under Law No. 14 of 2002, lacks explicit constitutional recognition, unlike the Administrative Court (PTUN), which is regulated under Law No. 51 of 2009. This study examines the need to reposition the Tax Court within the Indonesian judicial system, aligning it with Article 24 paragraph (2) of the 1945 Constitution to ensure judicial independence and consistency. Using a normative-empirical legal approach, the research integrates legal rules, principles, and doctrinal analysis with an evaluation of legislative ethics. Data sources include primary legal materials (Constitution, taxation laws, and judicial power laws), secondary materials (books, journals, articles), and tertiary references (legal dictionaries, encyclopedias). Data collection methods encompass observation, interviews, and documentation, analyzed through qualitative normative methods to provide holistic and contextual solutions. The findings highlight the necessity of repositioning the Tax Court under the Supreme Court to enhance judicial independence, as current oversight by the Ministry of Finance and the Supreme Court undermines its effectiveness. Additionally, amendments to Article 24 paragraph (2) of the 1945 Constitution are proposed to separate the Tax Court from the PTUN, improve legal certainty, and ensure a more effective and equitable tax adjudication system. This reform is crucial for strengthening Indonesia’s judicial framework and upholding the rule of law.